Spiritual Leadership dalam Kajian Manajemen Pendidikan Islam - Muh. Nur Islam Nurdin (Advances In Education Journal, 2026)
This article discusses the spiritual leadership model in educational institutions, in which spiritual leadership influences the existence and development of islamic educational institutions. The research method used in writing this study is a literature study (library reserarch). Literature research (library research) is a research conducted by researchers by collecting a number of books and scientific articles relating to the problem and research objectives. The findings in the study that spiritual leadership applied in islamic educational institutions provide a significant role. So that it will produce a superior and advanced institution.